Compact Wideband Microstrip Patch Antenna based on High Impedance Surface - Nelaturi, S.; Sarma, N. V. S. N. (Engineering, Technology & Applied Science Research, 2018)
A compact single probe feed asymmetrical semicircular fractal boundary patch antenna based on HIS (high impedance surface) is proposed for wide bandwidth at Wi-Fi band. Circular polarization operation can be obtained by embedding semi-circle fractal curves along the edges of the square patch antenna. The 10-dB return loss bandwidth is 15.13% (2.32GHz-2.70GHz). The 3-dB axial ratio bandwidth is 4.11% (2.38GHz-2.48GHz). The close relationship between simulation results and measured results establishes the antenna usefulness.